THE RELATIONSHIP OF INNOVATION WITH ORGANIZATIONAL PERFORMANCE - Suhag, Abdul karim; Solangi, Shafique Rahman; Larik, Raja Sohail Ahmed; Lakho, Muhammad Kamil; Tagar, Altaf Hussain (International Journal of Research -GRANTHAALAYAH, 2017)
This research study investigates the relationship of innovation with organizational performance of the telecommunication sector. The independent variables are process innovation, product innovation and organizational innovation as an organizational culture as moderating variable. The research is survey research in which questionnaire is administered to 200 employees that are concerned with innovation in telecom industry present in Islamabad and Rawalpindi to ensure reasonable response. The data was analyzed through the SPSS v.20 software. Results showed that product innovation, process innovation and organizational innovation has a positive impact on organization performance.